Sourcebook on the Foundations of Social Protection Delivery Systems - Lindert, Kathy (Washington, DC: World Bank, 2020)
The Sourcebook synthesizes real-world experiences and lessons learned of social protection delivery systems from around the world, with a particular focus on social and labor benefits and services. It takes a practical approach, seeking to address concrete “how-to” questions, including: How do countries deliver social protection benefits and services? How do they do so effectively and efficiently? How do they ensure dynamic inclusion, especially for the most vulnerable and needy? How do they promote better coordination and integration—not only among social protection programs but also programs in other parts of government? How can they meet the needs of their intended populations and provide a better client experience? The Sourcebook structures itself around eight key principles that can frame the delivery systems mindset: (1) delivery systems evolve over time, do so in a non-linear fashion, and are affected by the starting point(s); (2) additional efforts should be made to “do simple well”, and to do so from the start rather than trying to remedy by after-the-fact adding-on of features or aspects; (3) quality implementation matters, and weaknesses in the design or structure of any core system element will negatively impact delivery; (4) defining the “first mile” for people interface greatly affects the system and overall delivery, and is most improved when that “first mile” is understood as the weakest link in delivery systems); (5) delivery systems do not operate in a vacuum and thus should not be developed in silos; (6) delivery systems can contribute more broadly to government’s ability to intervene in other sectors, such as health insurance subsidies, scholarships, social energy tariffs, housing benefits, and legal services; (7) there is no single blueprint for delivery systems, but there are commonalities and those common elements constitute the core of the delivery systems framework; (8) inclusion and coordination are pervasive and perennial dual challenges, and they contribute to the objectives of effectiveness and efficiency.